Co-expression of CD25 and CD3 in atopic allergy and asthma. - Hamid, Q (1992)
In an attempt to identify the phenotype of the CD25+ cells previously demonstrated in late-phase allergic reactions in skin and nasal mucosa, and in the bronchial mucosa in atopic asthma we have investigated the co-expression of CD3 and CD25 using double immunofluorescent staining. Fluorescein isothiocyanate (FITC) conjugated anti-CD3 monoclonal antibody and a biotinylated anti-CD25 monoclonal antibody (which was later developed with Texas Red streptavidin) were applied simultaneously to cryostat sections or cytospins of freshly prepared samples. Skin and nasal biopsies were from antigen-induced late-phase reactions, and bronchial biopsies and cytospins of bronchoalveolar lavage cells were from subjects with moderate atopic asthma. Four to 14% of CD3+ cells in these tissues were CD25+ and 61-100% of CD25+ cells also expressed CD3. However, CD25 was also expressed on non-CD3+ cells, assumed to be non-T cells. These results were comparable to that observed with a positive control of a tuberculin-challenged skin biopsy. Thus the majority of cells expressing CD25 in various types of atopic allergic inflammation in man were T lymphocytes.